Histomorphological skin changes after surgical intervention - Neorčić, Martin; Fejsa Levakov, Aleksandra (Medicinski podmladak, 2022)
Introduction: The process of wound healing is best represented by an uninfected surgical wound. This process is represented by forming a granulation tissue, respectively with migration and proliferation of fibroblasts, neoangiogenesis and forming of extracellular matrix. Granulation tissue has been further replaced by scar made up of connecting tissue and in most cases the process is ended in 3 of 4 weeks. The whole process takes about 6 weeks and a newly formed scar has approximately 90% of hardness like the intact skin. The aim of this paper is the examination of histomorphological changes of the skin in per primam intentionem wound healing process. Material and methods: Six groups are formed based on the age of the wounds. In each group we searched for changes in epidermis, collagen fibrils, fibroblasts, capillaries, inflammatory infiltrate and hypodermis. Tissue biopsies are stained with H&E, Mallory trichrome, silver impregnation and immunohistochemistry staining methods for CD31, collagen IV and h-caldesmon. Results: Observing the wounds in different stages of healing we have spotted histomorphological changes that can be described chronologically. In each group we choose the most representative biopsy with a clear surgical cut and clear histological changes of the repairing process for that specific period. Conclusion: After the surgical incision, the process of skin repair takes place to form a new scar made of tissue somewhat different from the surrounding intact skin. The scar is visible and represents irregular architectonics of collagen fibers, deprivation of skin appendages in dermis, and thicker epidermis.